Report on professional attachment with Johnson & Johnson (ortho-clinical diagnostics). - Leong, Yi-ni. (2009)
The professional attachment arranged by NTU for the students is meant for the latter to gain an experience of working life relevant to their own course. Thus, this report serves to summarise and compile the several skills picked up and experience gained during this two months. Though basic skills are important fundamentally for work to be well done, to show oneself as a promising student and to-be credible working person requires much more than that. A lot depends on the attitude adopted and shown during the whole course of work.